2010
DOI: 10.1146/annurev.publhealth.012809.103538
|View full text |Cite
|
Sign up to set email alerts
|

How Experience Gets Under the Skin to Create Gradients in Developmental Health

Abstract: Social environments and experiences get under the skin early in life in ways that affect the course of human development. Because most factors associated with early child development are a function of socioeconomic status, differences in early child development form a socioeconomic gradient. We are now learning how, when, and by what means early experiences influence key biological systems over the long term to produce gradients: a process known as biological embedding. Opportunities for biological embedding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
447
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 602 publications
(467 citation statements)
references
References 85 publications
13
447
0
7
Order By: Relevance
“…A more recent focus within population sciences on how the broader environment "gets under the skin" suggests that this may be a key moment to look to the brain. Health psychologists have demonstrated that the broader environment becomes biologically embedded in the brain over the course of development (5,(13)(14)(15)(16)(17), but how does this yield observed variations within populations? Therefore, we argue that the critical juncture described for neuroscience research also poses an opportunity for population science research more broadly.…”
mentioning
confidence: 99%
“…A more recent focus within population sciences on how the broader environment "gets under the skin" suggests that this may be a key moment to look to the brain. Health psychologists have demonstrated that the broader environment becomes biologically embedded in the brain over the course of development (5,(13)(14)(15)(16)(17), but how does this yield observed variations within populations? Therefore, we argue that the critical juncture described for neuroscience research also poses an opportunity for population science research more broadly.…”
mentioning
confidence: 99%
“…Hertzman went on to solidify his analysis about the importance of what at the time he termed "biological embedding" through a series of studies, analyses of other studies, and reinterpretations of existing literature through this new life course health development lens. In addition to publishing several important articles of conceptual synthesis, Hertzman and Daniel Keating edited the volume Developmental Health and the Wealth of Nations in which they unpacked the impact of social gradients on health development and began to specify how different time-specific and pathway effects were at play early in development (Hertzman 1999;Keating and Hertzman 1999;Hertzman and Boyce 2010). They synthesized a wealth of evidence on how early experience affects a child's brain development, social and emotional functioning, and overall health capacities (Hertzman 1994;Keating and Hertzman 1999).…”
Section: The Maturation Of the Lchd Fieldmentioning
confidence: 99%
“…The same Canadian team that created the EDI and MDI is in the process of developing health development indices covering the entire child span, using the EDI to develop a pan-Canadian population health monitoring system (Guhn et al 2016b). In addition, the EDI has also been used as a measure in "cells to society" research that is examining the impact of social gradients and how that manifests in relationships to social epigenetics (Hertzman and Boyce 2010).…”
Section: Advance Lchd Measurement Capacity and Improve Study Design Tmentioning
confidence: 99%